Chemical composition and antimicrobial activity of Myristica fragrans & Elettaria cardamomum essential oil - Özkan, Osman Emre; Olgun, Çağrı; Güney, Betül; Gür, Mahmut; Güney, Kerim; Ateş, Saim (Kastamonu University, 2018)
Aim of study: The objectives in this study were to determine the chemical composition and antimicrobial activity of the essential oils from nutmeg (Myristica fragrans) and cardamom (Elettaria cardamomum).Material and Methods: The essential oil was obtained from nutmeg and cardamom seeds through hydrodistillation method. The chemical composition of nutmeg and cardamom essential oil was analyzed by GC-MS. The antimicrobial activity of essential oil was investigated against Bacillus subtilis DSMZ 1971, Candida albicans DSMZ 1386, Enterococcus faecalis ATCC 29212, Enterobacter aerogenes ATCC 13048, Enterococcus durans, Enterococcus faecium, Escherichia coli ATCC 25922, Klebsiella pneumoniae, Listeria monocytogenes, Listeria innocua, Pseudomonas aeruginosa DSMZ 50071, Pseudomonas fluorescence P1, Salmonella enteritidis ATCC 13076, Salmonella infantis, Salmonella kentucky, Salmonella typhimurium SL 1344, Staphylococcus aureus ATCC 25923 and Staphylococcus epidermidis DSMZ 20044 with minimum inhibitory concentration (MIC) method.Main results: GC-MS analyzes shows that γ-terpinene (19.16%), (-)-terpinen-4-ol (14.08%), α-pinene (6.75%), myristicin (6.18%), β-pinene (4.85%), sylvestrene (4.72%), elemicin (4.68%) and safrole (4.17%) identified in nutmeg essential oil. Also, α-terpinyl acetate (34.55%), eucalyptol (24.91%), (-)-terpinen-4-ol (10.63%), linalool (7.69%) and neryl butyrate (6.58%) compounds identified in cardamom essential oil as major compounds. Nutmeg and cardamom essential oil showed an antimicrobial activity against almost all test microorganisms.Research highlights: This study suggests that nutmeg and cardamom essential oil may be useful in the medicinal application and food industry as a preservative.
Keywords: Nutmeg; Cardamom; Essential oil; Antimicrobial activity; Muskat; Kakule; Uçucu yağ; Antimikrobiyal aktivite; 2. Zero hunger; 3. Good health